A comprehensive model for optical and thermal characterization of a linear Fresnel solar reflector with a trapezoidal cavity receiver. (November 2016) - Qiu, Yu; He, Ya-Ling; Wu, Ming; Zheng, Zhang-Jing
Abstract: In this paper, a comprehensive numerical model was developed by coupling Monte Carlo Ray Tracing (MCRT) and Finite Volume Method (FVM) for simulating the energy conversion process in the linear Fresnel reflector (LFR) with a Trapezoidal Cavity Receiver (TCR). Based on the model, firstly, the optical performance of a typical LFR was studied, followed by analyzing its heat transfer characteristics and thermal performance at various conditions. Then, the effects of key parameters were investigated. Finally, a LFR prototype was simulated to illustrate the application of the model. The results indicate that the solar fluxes on the absorber tubes exhibit non-uniform characteristics which would result in the non-uniform temperatures. The annual optical efficiency of 60.1%–44.7% from the equator to N50° and the collector efficiency of 48.3%–72.0% for the superheating section at normal incidence can be achieved, respectively. Moreover, the heat transfer characteristic study reveals that the radiation loss from the tubes is the dominant mode and contributes around 81%–87% at typical conditions. Parameter studies indicate that the energy absorbed by the glass which influences the heat loss obviously should be considered in the heat loss study of TCR. And the heat loss from the tubes increases rapidly with the coating emissivity, so the coating with low emissivity should be recommended for the TCR. In addition, the application in the realistic LFR indicates that the present model is an exercisable and useful tool for the LFR. Highlights: A new optical-thermal model for a linear Fresnel solar reflector is presented. Solar radiation transfer and energy conversion processes are simulated integrally. Yearly optical efficiency of 60.1%–44.7% from the equator to N50° is revealed. Heat transfer characteristics and thermal performance of the receiver are analyzed. Radiation loss from tubes is found to be dominant and contributes around 81%–87%.